2018
DOI: 10.1038/s41598-018-24707-2
|View full text |Cite
|
Sign up to set email alerts
|

The association between skin auto-fluorescence of palmoplantar sites and microvascular complications in Asian patients with type 2 diabetes mellitus

Abstract: Skin auto-fluorescence (SAF) has generated broad interest about the prospects for non-invasive advanced glycation end product assessment and its direct interplay with the development of microvascular complications, but clinical application of the existing SAF measuring of non-palmoplantar sites in non-Caucasian subjects with dark skin type is still controversial. Here, we tested the diabetic complication screening performance of a novel SAF measuring system in Asian type 2 diabetes mellitus (T2DM) subjects. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The prevalence of DR in the sample ranged from 31.3% to 75.0% among diabetic participants. All studies measured AGEs in the forearm with SAF, except one that measured AGEs in the palm of the hand 44 . The device used to measure SAF differed among studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence of DR in the sample ranged from 31.3% to 75.0% among diabetic participants. All studies measured AGEs in the forearm with SAF, except one that measured AGEs in the palm of the hand 44 . The device used to measure SAF differed among studies.…”
Section: Resultsmentioning
confidence: 99%
“…There is a paucity of information on test analysis and one of the studies does not show SAF test specificity data for DR, so we decided to use the data for microvascular complications in general. 44 There are unreported data in the studies, so it is not possible to assess whether some factors were considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent study by Kim et al. [ 23 ] found that, using a novel SAF instrument, SAF was significantly higher at palmoplantar sites in Asian subjects with T2D complications, as compared to those without. No differences were observed between these groups in SAF of non-palmoplantar sites.…”
Section: Discussionmentioning
confidence: 96%